Successful implementation of online educational lectures of the German Society for Radiation Oncology (DEGRO) - Büttner, Marcel; Melton, Philip; Fietkau, Rainer; Petersen, Cordula; Krause, Mechthild; Borgmann, Kerstin; Wolf, Ulrich; Niyazi, Maximilian; Christiansen, Hans; Höller, Ulrike; Schmitt, Daniela; Käsmann, Lukas; et al. (Strahlentherapie und Onkologie, 2023)
Purpose: Modern digital teaching formats have become increasingly important in recent years, in part due to the COVID-19 pandemic. In January 2021, an online-based webinar series was established by the German Society for Radiation Oncology (DEGRO) and the young DEGRO (yDEGRO) working group. In the monthly 120-minute courses, selected lecturers teach curricular content as preparation for the board certification exam for radiation oncology. Methods: The evaluation of the 24 courses between 01.2021 and 12.2022 was performed using a standardized questionnaire with 21 items (recording epidemiological characteristics of the participants, didactic quality, content quality). A Likert scale (1–4) was used in combination with binary and open-ended questions. Results: A combined total of 4200 individuals (1952 in 2021 and 2248 in 2022) registered for the courses, and out of those, 934 participants (455 in 2021 and 479 in 2022) later provided evaluations for the respective courses (36% residents, 35% specialists, 21% medical technicians for radiology [MTR], 8% medical physics experts [MPE]). After 2 years, 74% of the DEGRO Academy curriculum topics were covered by the monthly webinars. The overall rating by participants was positive (mean 2021: 1.33 and 2022: 1.25) and exceeded the curriculum offered at each site for 70% of participants. Case-based learning was identified as a particularly well-rated method. Conclusion: The DEGRO webinar expands the digital teaching opportunities in radiation oncology. The consistently high number of participants confirms the need for high-quality teaching and underlines the advantages of e‑learning methods. Optimization opportunities were identified through reevaluation of feedback from course participants. In its design as a teaching format for a multiprofessional audience, the webinar series could be used as a practice model of online teaching for other disciplines.
CRIS-Team Scopus Importer:2023-11-03
Keywords: e‑learning; Medical education; Online webinar; Radiation oncology; Teaching format